Pengaruh Infusa Daun Kelor (Moringa oleifera) terhadap Penurunan Kadar Glukosa Darah dan Kolesterol Total pada Mencit (Mus musculus) yang Mengalami Ulkus Diabetikum: Pengaruh Infusa Daun Kelor (Moringa oleifera) - Helen Debora Napitupulu; Jekson Martiar Siahaan; Batara Simangunsong (Universitas Methodist Indonesia, 2024)
Background: Diabetes mellitus is a chronic disease in the form of metabolic disorders, which is characterized by blood glucose levels (BGL) that exceed normal limits and are accompanied by disorders of carbohydrate, lipid, and protein metabolism, as a result of abnormalities in insulin secretion. Diabetics are known to have slow wound healing. Moringa oleifera leaves contain flavonoid compounds, which can reduce glucose absorption. Objective: This study aims to determine the effect of Moringa leaf infusion on blood sugar levels, glucose tolerance, cholesterol levels, body weight, and speed of wound healing in mice model. Method : A total of 25 male mice aged 2-3 months weighing 25-30 grams were divided into 5 experimental groups namely: negative control, positive control, 10% Moringa infusion, 20% infusion, 30% infusion. The negative control was not given any treatment. Positive controls were induced by high fat diet and PTU and given sucrose for 3 weeks. The infusion group was the same as the positive control but at the end of each week, 10%, 20%, and 30% Moringa leaf infusion were given successively. Moringa leaf intervention was given for 3 weeks after feed induction and observations were made at that range. The wound was made after feeding induction on the back 1 cm long. Result : Moringa leaf infusion had a significant effect on reducing the levels of each variable, namely a dose of 10% on body weight, a dose of 30% on KGD, 20% on KGD with glucose loading, 20% on cholesterol, and 20% on wound closure, which proved based on the results of statistical tests. Conclusion: Moringa leaf infusion can reduce blood sugar levels, blood sugar levels by loading glucose, cholesterol levels, body weight, and accelerate wound healing in mice induced by sucrose, high fat diet, and PTU.